Perilaku Konsumen Gula Putih Bermerek dan Tidak Bermerek di Kabupaten Jember - Safira, Maulida Rachma; Aji, Joni Murti Mulyo (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
The purpose of this study was to determine the factors that influence consumer decisions in buying branded and unbranded white sugar, to determine the level of consumer satisfaction with branded and unbranded white sugar and to determine the factors that influence the level of consumer satisfaction with branded and unbranded white sugar in Jember Regency. This research was conducted using 200 respondents. The analysis tools used are logistic regression analysis, CSI analysis (Customer Satisfaction Index) and factor analysis. The results showed that the factors that significantly influence consumer decisions in buying branded and unbranded white sugar are income and number of family members. The CSI measurement results show that the consumer satisfaction index of unbranded and unbranded white sugar is in the fulfilled criteria, with a CSI value of 74.48% for branded and 70.30% for unbranded sugar. The results of the factor analysis show that there are three new factors related to the satisfaction level of consumers of branded and unbranded white sugar, namely the money value factor (product cleanliness and sugar prices), availability considerations factor (house distance, the ease of obtaining sugar, advertising, information from friends and information from family), and brand attribute factor (brand, color, packaging design and packaging weight).